Electromagnetic Compatibility Technology of Communication Cables in Coal Mine Monitoring System - XIE Hao, ZHU Xiaojie, GAO Wenping, XIE Junsheng (Meikuang Anquan, 2020)
Some problems are discussed about the electromagnetic radiation of mine communication cables, the interference of electromagnetic fields on cables and ports of mine communication cables. The signal crosstalk of capacitive coupling, inductive coupling between adjacent cables in underground coal mine and the influence of distribution parameters of mine communication cables on the electromagnetic compatibility is analyzed and studied in detail, and the solutions for these problems are proposed.